ANALISIS YURIDIS TERHADAP PENGATURAN PERAN TNI DALAM MENANGGULANGI TINDAK PIDANA NARKOTIKA - Irwan Charles Sitompul; Bismar Nasution; Suhaidi Suhaidi; Mahmud Mulyadi (Universitas Sumatera Utara, 2018)
ABSTRACT One of the cooperation undertaken BNN with TNI that has the task of maintaining security and defense Indonesia where cooperation set out in the Memorandum of Understanding between the National Narcotics Agency with the Indonesian National Army is No. NK/29/V/ 2015/BNN, No. Kerma 14/V/2015 dated May 13, 2015 on military assistance to BNN in the framework of the Prevention and Combating Drug Abuse and Illicit Narcotics and Narcotics Precursor and Rehabilitation abusers and addicts Narcotics and Narcotics Precursor. The essence of this MoU is an optimization function of supporting community empowerment and anti-abuse and illicit trafficking of narcotic drugs and precursors; dissemination of information and advocacy on the prevention of abuse and illicit trafficking of narcotics and precursors as well as the inspection of drug trials against military personnel. Keywords: Narcotics, the Indonesian Armed Forces and Law Enforcement